Diseño y evaluación de biodigestor para aprovechamiento de residuos de la industria porcina y generación de energía - Carrión Quezada, Willan Adrián (2025)
This project offers an efficient structural alternative for the management This project proposes an efficient structural alternative for the management of pork waste through the implementation of an optimized biodigester system. This design not only allows for proper waste management, but also facilitates the production of biogas as a renewable energy source. The study covers a comprehensive analysis that includes the composition of the biogas obtained, determining the optimal concentration of methane to maximize electricity generation. The energy efficiency of the system was evaluated, expressed in terms of biogas production per cubic meter generated and its capacity to power an electrical generator. In addition, detailed structural analyzes were carried out to ensure the stability and durability of the system, considering factors such as loads per square meter, the weight of the components and the self-weight of the structure to withstand the operating conditions on a pig farm. Likewise, the operational viability of the biodigester in the upper part of the province of El Oro was analyzed, evaluating its impact on sustainable waste management. The results obtained show the potential of biogas as a renewable energy source and highlight the structural benefits of the proposed design, ensuring its efficiency and resistance. Finally, its contribution to the reduction of environmental pollution and the energy self-sufficiency of the pork sector is highlighted.